DIMENSIONS OF SERVICE QUALITY-AN EMPIRICAL STUDY ON COMMUTERS USING DELHI METRO - Kumar, Sunil; Siddiquei, Mohd Imran; Muneeb, Syed Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to find out the different factors related to quality of service in Delhi metro firm and to pinpoint the most domineering element in service quality by Delhi metro. In the present study we have used Descriptive research design, in order to get more insight about the research issue in the concern context. In our study there are 240 respondents who regular travelers of Delhi metro. In sample units, we concern to commuters to get the response about various dimensions of service quality of Delhi metro. There are five dimension of service quality of Delhi metro. They are reliability, tangibility, empathy, assurance, responsiveness. Tangibility factor is the max paramount point in utility choiceness. All the dimension of service quality contributes in the overall service quality of Delhi metro. Reliability has a better impact over service quality on Delhi metro among other service quality dimension. Notable number of research and surveys has been conducted on service quality of different transport means and various dimensions have been explained.